Taming posterior polar cataract – My way of small incision cataract surgery - PP Soumya (Kerala Journal of Ophthalmology)
Posterior polar cataracts (PPCs) present a challenging situation for surgeons due to the high likelihood of intraoperative issues such as posterior capsular rupture and aphakia. It is widely recognized that patients with PPC typically have a thin posterior capsule, which is densely attached to the cataract, making it fragile. Although various surgical techniques have been suggested for addressing this specific type of cataract, achieving successful outcomes without complications remains a significant challenge for many surgeons. In developing countries, aspiring surgeons may not have extensive experience with phacoemulsification. This study explores the safe application of small incision cataract surgery in such cases.